Saponin Modified Clay For Crude Palm Oil Bleaching - Fahrizal Ayub Kalidikalam; Patricia Grace Dei Evita Tanzil Halili; Shella P Santoso; Suryadi Ismadji (Fakultas Teknik, Universitas Katolik Widya Mandala Surabaya, 2020)
Bleaching of crude palm oil (MGS) is a mandatory step for producing edible palm oil. Bleaching agent, known as bleaching earth, is used as the decolorization agent. Bleaching earth acts as adsorbent to adsorb carotenoid and other organic content in MGS. Bentonite is the common decolorization agent used in the bleaching process. Activation of bentonite is needed prior to enhanced the adsorptive ability. In this study, the bentonite was fabricated by using saponin surfactant to enlarge the surface area, and thus, improving the adsorption capacity of bentonite. The activation of bentonite was conducted by impregnating the bentonite particles with saponin solution at various mass ratio; specifically, bentonite to saponin ratios of 100: 1, 200: 1, 300: 1, 400: 1, and 500: 1 were applied. The impregnation, or activation, temperature of 40 and 50˚C was chosen. The succeed of the saponin impregnation was characterized using a Fourier Transform Infrared (FTIR) spectroscopy analysis. The alteration of bentonite cation exchange capacity (CEC) value before and after impregnation was evaluated. The bleaching performance of the saponin modified bentonite was assessed by determining the amount of carotenoid compound removed. Furthermore, the change in free-fatty acid value of MGS (after bleaching) was also assessed. The bleaching process was carried out by mixing the bentonite into MGS at a temperature of 90˚C for 10 minutes. The bleaching process result shows that the rarasaponin modified bentonite able to adsorp 310 mg of carotenoid per g of the adsorbent.